Acid production in dental plaque after exposure to probiotic bacteria - Keller, Mette K; Twetman, Svante (BMC oral health, 2012)
Background The increasing interest in probiotic lactobacilli in health maintenance has raised the question of potential risks. One possible side effect could be an increased acidogenicity in dental plaque. The aim of this study was to investigate the effect of probiotic lactobacilli on plaque lactic acid (LA) production in vitro and in vivo . Methods In the first part (A), suspensions of two lactobacilli strains ( L. reuteri DSM 17938 , L. plantarum 299v) were added to suspensions of supragingival dental plaque collected from healthy young adults (n=25). LA production after fermentation with either xylitol or fructose was analyzed. In the second part (B), subjects (n=18) were given lozenges with probiotic lactobacilli ( L. reuteri DSM 17938 and ATCC PTA 5289) or placebo for two weeks in a double-blinded, randomized cross-over trial. The concentration of LA in supragingival plaque samples was determined at baseline and after 2 weeks. Salivary counts of mutans streptococci (MS) and lactobacilli were estimated with chair-side methods. Results Plaque suspensions with L. reuteri DSM 17938 produced significantly less LA compared with L. plantarum 299v or controls (p<0.05). Fructose gave higher LA concentrations than xylitol. In part B, there were no significant differences in LA production between baseline and follow up in any of the groups and no differences between test and placebo were displayed. The salivary MS counts were not significantly altered during the intervention but the lactobacilli counts increased significantly in the test group (p<0.05). Conclusion Lactic acid production in suspensions of plaque and probiotic lactobacilli was strain-dependant and the present study provides no evidence of an increase in plaque acidity by the supply of selected probiotic lactobacilli when challenged by fructose or xylitol. The study protocol was approved by The Danish National Committee on Biomedical Research Ethics (protocol no H-2-2010-112). Trial registration NCT01700712